Problematika Pertimbangan Hukum dalam Putusan Kasasi Mahkamah Agung Nomor 647 K/PDT.SUS-Pailit/2021 - Callysta Qabil; Arief Suryono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the legal basis used by judges in granting the cassation request in Mahkamah Agung Decision Number 647 K/PDT.SUS-PAILIT/2021 and its implications for the legal protection of the insured. This research is a normative legal study using a statutory and case approach, utilizing primary and secondary legal materials collected through literature studies. The analysis is conducted using a syllogistic method and a deductive reasoning pattern. The findings indicate that if the insured does not agree with the homologation agreement or if there is a counterproductive element, there is a legal basis for filing a cassation under Article 286 of Law Number 37 of 2004.